IMPLEMENTASI PRINSIP PRINSIP SYARIAH EKONOMI PADA UMKM DI DESA TENILO - William Indra S Mooduto; Andini Putri Tahir; Dita Aditiya Kasim (LPPM Universitas Bina Mandiri Gorontalo, 2023)
Sharia economics in micro, small, and medium enterprises (MSMEs) in Tenilo Village. MSMEs have a very important role in the village economy, but many still do not understand and implement sharia principles properly. This study uses a community service method with a qualitative approach to identify problems and provide practical solutions. The results found showed that many MSMEs in Tenilo Village experienced obstacles in implementing sharia principles, but there was a significant improvement after training and mentoring related to sharia economic principles, such as the prohibition of usury and fair transactions.